KOMPARASI PSIKOLOGI AGAMA BARAT DENGAN PSIKOLOGI ISLAMI MENUJU REKONSTRUKSI PSIKOLOGI ISLAMI - Zubaedi Zubaedi (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
This article discusses the comparison between the psychology of religion that comes from tradition West with Islamic Psychology unearthed from the Quran and Hadith. The study assumes that epistemologically, the two poles of this psychology have differing views on the potential of human religiosity, but in parts of certain thoughts can can be connected. There are two issues can connect both buildings psychology. Psychology of religion although not explicitly alluded to religion, but the descriptions of the appreciation of the spiritual aspects of humans simply can not be avoided. Some defecate great Western psychologist who confirmed the existence of the religious instinct. Vary the terms they use, but the substantial question is a form of encouragement that causes humans tend to acknowledge the existence of a supernatural agent